(untitled) (Linguist, 2025)
The development of cognitive sciences enables the formation of advanced conceptions of narrative structures, as representational mental structures that fall into the overall cognitive environment of the mind/brain. In this paper, we will discuss aspects of the aforementioned development concerning some primitives and abilities on which these structures are based. This is done through two steps: - Determining some conceptual primitives that constitute the design of narrative cognition structures, and derive its significance and cognitive efficiency from the network of interface interactions between these primitives and other mental systems. - Determining some human qualitative cognitive capacities, which shed a revealing light on narrative discourse working, on our interaction with it and on our passion for it. These capacities are: (a) Theory of Mind, which is manifested in our ability to assign mental states to other people to explain their behavior, including fictional characters in narrative structures. It is an ability that the narrative discourse urgently requires in us, and that makes this discourse, and literature in general, possible; (b) metarepresentation, an evolved cognitive ability to keep track of sources of our mental representations. It is a developed component of the Theory of Mind. The attribution of mental states to literary characters is crucially mediated by the workings of this component. Thus, fictional narratives rely on, manipulate, and titillate our tendency to keep track of who thought, wanted, and felt what, when and where.